Further evidences of an emerging stingless bee-yeast symbiosis - de Paula, Gabriela Toninato; Melo, Weilan Gomes da Paixão; Castro, Ivan de; Menezes, Cristiano; Paludo, Camila Raquel; Rosa, Carlos Augusto; Pupo, Mônica Tallarico (Frontiers in Microbiology, 2023)
Symbiotic interactions between microorganisms and social insects have been described as crucial for the maintenance of these multitrophic systems, as observed for the stingless bee Scaptotrigona depilis and the yeast Zygosaccharomyces sp. SDBC30G. The larvae of S. depilis ingest fungal filaments of Zygosaccharomyces sp. SDBC30G to obtain ergosterol, which is the precursor for the biosynthesis of ecdysteroids that modulate insect metamorphosis. In this work, we find a similar insect-microbe interaction in other species of stingless bees. We analyzed brood cell samples from 19 species of stingless bees collected in Brazil. The osmophilic yeast Zygosaccharomyces spp. was isolated from eight bee species, namely Scaptotrigona bipuctata, S. postica, S. tubiba, Tetragona clavipes, Melipona quadrifasciata, M. fasciculata, M. bicolor and Partamona helleri. These yeasts form pseudohyphae and also accumulate ergosterol in lipid droplets, similar to the pattern observed for S. depilis. The phylogenetic analyses including various Zygosaccharomyces revealed that strains isolated from the brood cells formed a branch separated from the previously described Zygosaccharomyces species, suggesting that they are new species of this genus and reinforcing the symbiotic interaction with the host insects.